Effect of sex and seasons of the year on hematologic and serum biochemical variables of captive brown brocket deer (Mazama gouazoubira) - Camargo, Clara M.s. [UNESP] (2013)
The Brown brocket deer (Mazama gouazoubira) is the most common free-living and captive deer in South America, especially in Brazil, and has great ecological and scientific significance. However, data on hematological and biochemical parameters in brown brocket deer are scarce. The goal of this study was to establish reference ranges for hematological and biochemical parameters of Mazama gouazoubira, comparing differences during the seasons of the year and between sex. Blood samples from ten adult healthy brown brocket deer (6 female and 4 male) were collected during daytime, monthly, during 12 months. The animals were maintained in individual stable, protected from noise and fed ad libitum with commercial ration and green fodder. For blood collection, animals were submitted to physical restrain for no longer than 2 minutes. The following parameters were determined: red blood cell count (RBC), haemoglobin concentration, packed cell volume (PCV), mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC), white blood cell count (WBC), platelet count, enzyme activity of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and gamma-glutamyl transferase (GGT) and serum levels of alkaline phosphatase (ALP), creatine kinase (CK), total protein (TP), albumin, cholesterol, total calcium, ionic calcium, sodium, potassium, magnesium, triglycerides, creatinine and urea. Values were compared according to season and sex. RBC count, WBC count and MCV suggested seasonal influence. Haemoglobin concentration, PCV and MCV were influenced by sex. Serum concentration of total calcium, ionic calcium, sodium, potassium and magnesium were influenced by season. Serum magnesium was also influenced by sex. The blood parameters herein reported may be useful as reference values for diagnostic and prognostic purposes in captive brown-brocket deer.